2012
DOI: 10.1055/s-0032-1307601
|View full text |Cite
|
Sign up to set email alerts
|

Michael Acceptor Approach to the Design of New Salvinorin A- Based High Affinity Ligands to the Kappa-Opioid Receptor

Abstract: The neoclerodane diterpenoid salvinorin A is a major secondary metabolite isolated from the psychoactive plant Salvia divinorum. Salvinorin A has been shown to have high affinity and selectivity for the κ-opioid receptor (KOR). To study the ligand-receptor interactions that occur between salvinorin A and the KOR, a new series of salvinorin A derivatives bearing potentially reactive Michael acceptor functional groups at C-2 was synthesized and used to probe the salvinorin A binding site. The κ-, δ-, and μ-opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…1 H NMR (500 MHz, CDCl 3 ): δ 7.38 (d, J = 1.88 Hz, 1H), 6.33 (d, J = 1.89 Hz, 1H), 5.65 (dd, J = 5.01, 11.99 Hz, 1H), 5.10 (dd, J = 19.97, 28.28 Hz, 1H), 5.08 (d, J = 9.32 Hz, 2H), 3.73 (s, 3H), 2.76 (m, 1H), 2.37 (dd, J = 5.02, 13.53 Hz, 1H), 2.29 (dd, J = 6.36, 13.55 Hz, 2H), 2.16 (m, 3H), 2.15 (s, 3H), 2.08 (s, 3H), 1.80 (m, 1H), 1.62 (m, 3H), 1.48 (s, 3H), 1.12 (s, 3H). 13 (2S,4aR,6aR,7R,9S,10aS,10bR)-Methyl 9-Acetoxy-2-(2-formylfuran-3-yl)-6a,10b-dimethyl-4,10-dioxododecahydro-1Hbenzo[f ]isochromene-7-carboxylate (49). A solution DMSO (0.08 mL, 27 equiv) in CH 2 Cl 2 (0.5 mL) was added to a solution of oxalyl chloride (0.05 mL, 14 equiv) in CH 2 Cl 2 (2 mL) at −78 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (500 MHz, CDCl 3 ): δ 7.38 (d, J = 1.88 Hz, 1H), 6.33 (d, J = 1.89 Hz, 1H), 5.65 (dd, J = 5.01, 11.99 Hz, 1H), 5.10 (dd, J = 19.97, 28.28 Hz, 1H), 5.08 (d, J = 9.32 Hz, 2H), 3.73 (s, 3H), 2.76 (m, 1H), 2.37 (dd, J = 5.02, 13.53 Hz, 1H), 2.29 (dd, J = 6.36, 13.55 Hz, 2H), 2.16 (m, 3H), 2.15 (s, 3H), 2.08 (s, 3H), 1.80 (m, 1H), 1.62 (m, 3H), 1.48 (s, 3H), 1.12 (s, 3H). 13 (2S,4aR,6aR,7R,9S,10aS,10bR)-Methyl 9-Acetoxy-2-(2-formylfuran-3-yl)-6a,10b-dimethyl-4,10-dioxododecahydro-1Hbenzo[f ]isochromene-7-carboxylate (49). A solution DMSO (0.08 mL, 27 equiv) in CH 2 Cl 2 (0.5 mL) was added to a solution of oxalyl chloride (0.05 mL, 14 equiv) in CH 2 Cl 2 (2 mL) at −78 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The most striking feature of 1 is the lack of a basic nitrogen, which was once thought to be required for opioid receptor binding . This has led to the proposal of several binding models including one based on the recently solved KOR crystal structure. , …”
Section: Introductionmentioning
confidence: 99%
“…SA (purity: 99% by high‐performance liquid chromatography) was isolated from S. divinorum leaves, purchased from The Sage Wisdom Salvia Shop (Malibu, CA, USA) by one of the authors (J.K.Z.). PR‐37 and PR‐38 were synthesized from SA at the Department of Pharmacognosy, University of Mississippi, USA, as described earlier (Polepally et al ., 2013; 2014). Nor‐binaltorphimine dihydrochloride, β‐FNA hydrochloride, NLTR hydrochloride and AM 251 were purchased from Tocris Bioscience (Ellisville, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we characterized the antiscratch effect of the selective KOR agonist salvinorin A (SA), a natural diterpenoid isolated from the Mexican plant Salvia divinorum , and its two Michael acceptor‐type analogues, methyl salvinorin B‐2‐ O ‐malonate (PR‐37) and 2‐ O ‐cinnamoylsalvinorin B (PR‐38) (Fichna et al ., ; Polepally et al ., ; Polepally et al ., ). In the in vitro studies, these two analogs displayed high affinity at KOR with K i values of 2.0 ± 0.9 and 9.6 ± 2.0 nM for PR‐37 and PR‐38, respectively (Polepally et al ., 2013; 2014), and potently inhibited adenylate cyclase in live HEK293 cells with EC 50 values of 137 ± 15 and 7 ± 1 nM respectively (Polepally et al ., 2013; 2014). Of note, recently we showed that PR‐38 has neither hallucinogenic nor anxiolytic or anxiogenic effects in mice (Salaga et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Within this group, 22-thiocyanatosalvinorin A (6) from our laboratory represents the first example of an irreversible (covalently bound) salvinorin-A-derived ligand to KOR (Yan et al 2009). Some modifications at C-2, especially those involving introduction of aromatic moieties, result in significant changes in the pharmacological profile of analogs, from KOR selective to MOR/KOR dual affinity (Harding et al 2005a;Beguin et al 2008;Tidgewell et al 2008;Prevath-Smith et al 2011;Polepally et al 2014) and even to highly selective MOR (mu-opioid receptor) ligands (Tidgewell et al 2008) (Figure 4.3). These compounds may serve as good leads for further development of non-hallucinogenic and non-addictive analgesic agents.…”
Section: Chemistrymentioning
confidence: 99%